Usage of C-reactive protein testing in the diagnosis and monitoring of psoriatic arthritis (PsA): results from a real-world survey in the USA and Europe - Ogdie, A; Tillett, W; Booth, N; Howell, O; Schubert, A; Peterson, S; Chakravarty, SD; Coates, LC (Springer Nature, 2022)
Introduction C-reactive protein (CRP) is an important non-specific marker of both acute and chronic inflammation and can be elevated in patients with psoriatic arthritis (PsA). However, the use of CRP testing in the management of PsA can vary. This study investigated how CRP testing is implemented in real-world clinical practice for disease management of PsA. Methods A point-in-time survey of rheumatologists and dermatologists and their next six consulting patients with PsA was conducted in France, Germany, Italy, Spain, UK (EU5), and the USA between June and August 2018. Use of CRP testing was obtained by asking the physician to state (yes/no) whether CRP was used to aid PsA diagnosis and/or to monitor the patient’s disease activity. The number of CRP tests conducted in the last 12 months for each patient enrolled was provided. Results Data were collected for 2270 patients (USA, n = 595; EU5, n = 1675). In the EU5, CRP testing was conducted to aid diagnosis in 78.7% of patients (vs. 43.4% in USA) and CRP was used to monitor disease activity in 72.0% (vs. 34.6% in USA). The majority (80.9%) of patients in the EU5 had at least one CRP test in the last 12 months compared to 42.9% in the USA. Patients treated by rheumatologists (vs. dermatologists) were at least 50% more likely to have CRP tested for monitoring purposes, this difference being most pronounced in the USA. In the EU5, CRP testing was conducted a mean ± standard deviation of 2.7 ± 1.7 times during the last 12 months, versus 2.0 ± 1.4 in the USA. Conclusions CRP was more commonly used for the diagnosis and monitoring of PsA in Europe compared to the USA and was more commonly ordered by rheumatologists than dermatologists. In the absence of a better serum biomarker of inflammation, more data are needed to understand how CRP testing should be used in the diagnosis and management PsA.